2004
DOI: 10.1111/j.1096-0031.2004.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome data alone are not enough to unambiguously resolve the relationships of Entognatha, Insecta and Crustacea sensu lato (Arthropoda)

Abstract: An analysis of the relationships of the major arthropod groups was undertaken using mitochondrial genome data to examine the hypotheses that Hexapoda is polyphyletic and that Collembola is more closely related to branchiopod crustaceans than insects. We sought to examine the sensitivity of this relationship to outgroup choice, data treatment, gene choice and optimality criteria used in the phylogenetic analysis of mitochondrial genome data. Additionally we sequenced the mitochondrial genome of an archaeognatha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 114 publications
(162 reference statements)
6
101
0
Order By: Relevance
“…Even rapidly-evolving mitochondrial genes often show support for deep notes. Cameron et al (2004) reported that 18S rRNA had the best phylogenetic signal ratio using Neighbour-joining tree. Mitochondrial Cytochrome Oxidase I (mtCOI) gene proved to be useful to resolve evolutionary relationships among closely related species for a wide range of taxa, especially for calanoid copepods and euphausiids (Bucklin 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Even rapidly-evolving mitochondrial genes often show support for deep notes. Cameron et al (2004) reported that 18S rRNA had the best phylogenetic signal ratio using Neighbour-joining tree. Mitochondrial Cytochrome Oxidase I (mtCOI) gene proved to be useful to resolve evolutionary relationships among closely related species for a wide range of taxa, especially for calanoid copepods and euphausiids (Bucklin 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic performance of different genes is related to their particular rates of evolution. The three protein-coding genes, atp6, atp8, and nad4L, are the fastest evolving genes, while COX subunits and Cyt b show much-slower overall rates of evolution (Russo et al 1996;Zardoya and Meyer 1996; Cameron et al 2004). Cox1 is the most conserved gene in terms of amino acid evolution.…”
Section: Phylogenetic Analyses In This Studymentioning
confidence: 99%
“…Different optimality criteria and dataset compilation techniques have been applied to find the best method of analyzing complex mitogenomic data (Stewart and Beckenbach 2009, Cameron et al 2004, Castro and Dowton 2005, Kim et al 2005. In this paper, we compared the effect of partitioning according to different protein-coding genes (NADH, COX, COX + Cyt b, and ATP) and different regions in rRNA (rRNA(C) (small subunit ribosomal RNA (rrnS) (III) + large subunit ribosomal RNA (rrnL) (III + IV + V)) and rRNA(V) (rrnS (I + II) + rrnL (I + II + VI))).…”
Section: Phylogenetic Relationships Within the Orthopteramentioning
confidence: 99%
“…Dataset alignment strategies may also affect the recovered topology (Cameron et al 2004;Cameron et al 2009). Comparison of the topologies recovered from the datasets aligned by Clustal and Muscle (both with third codon positions excluded) indicated that the topology produced from the Muscle alignment was more congruent with expected relationships than the Clustal alignment.…”
Section: Phylogenetic Analysis and Considerationsmentioning
confidence: 99%